Automated control for process optimization in banana production in Ecuador: A systematic review (Innovation & Development in Engineering and Applied Science, 2026)
Banana production in Ecuador faces challenges in operational efficiency and sustainability, with limited adoption of automatic control technologies that optimize processes and reduce environmental impacts. The objective of this study is to identify technological tools with a circular approach to implement automatic control systems that improve productivity, stability, and sustainability in the banana production chain.The literature review enabled the identification and selection of research from reliable sources, providing a solid foundation for the development of the study. Various tools with circular approaches were identified as fundamental to research on automatic control in banana production in Ecuador.The methodology employed is a scoping review, divided into three phases: planning, execution, and dissemination. Platforms focused on statistical variable analysis were used, allowing system performance optimization through data collection and analysis. This resulted in improved efficiency, stability, and responsiveness of automatic control systems.Additionally, the use of PLC and SCADA systems was highlighted as an effective methodology for designing automated control prototypes that benefit companies. These systems proved effective in improving efficiency and operational response by 20–30%. The review also highlights the positive impact of programmable logic controllers (PLCs) in the Latin American industry, enhancing sustainability and competitiveness in global markets.
Keywords: Automatic control; PLC; SCADA; banana production; industrial sustainability; industrial automation; process optimization